Current and Future Treatment Strategies for Rhabdomyosarcoma - Chen, Celine; Dorado Garcia, Heathcliff; Scheer, Monika; Henssen, Anton G. (Frontiers in Oncology, 2019)
Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in children, and can be subcategorized histologically and/or based on PAX-FOXO1 fusion gene status. Over the last four decades, there have been no significant improvements in clinical outcomes for advanced and metastatic RMS patients, underscoring a need for new treatment options for these groups. Despite significant advancements in our understanding of the genomic landscape and underlying biological mechanisms governing RMS that have informed the identification of novel therapeutic targets, development of these therapies in clinical trials has lagged far behind. In this review, we summarize the current frontline multi-modality therapy for RMS according to pediatric protocols, highlight emerging targeted therapies and immunotherapies identified by preclinical studies, and discuss early clinical trial data and the implications they hold for future clinical development.